Mikro-i makroekonomiczne czynniki kształtowania decyzji o wypłatach dywidend przez spółki notowane na Giełdzie Papierów Wartościowych w Warszawie - Kowerski, Mieczysław (Micro and macroeconomic factors influencing dividend disbursement decisions on Warsaw Stock Exchange, 2006)
In the paper, using the micro-macro logit models concept, it was shown that the dividends disbursement decisions made by firms quoted on Warsaw Stock Exchange in the years 1996 2004 depended on both microeconomic factors connected with specific economic – financial condition of each firm and macroeconomic factors. During prosperity periods the propensity to pay dividends was higher then during recession periods.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 216-227